Immunogenicity and safety of an inactivated quadrivalent influenza vaccine in healthy adults: a phase II, open‐label, uncontrolled trial in Japan. (16th October 2015) - Tsurudome, Yukari; Kimachi, Kazuhiko; Okada, Yusuke; Matsuura, Kenta; Ooyama, Yusuke; Ibaragi, Kayo; Kino, Yoichiro; Ueda, Kohji
Abstract Two antigenically distinct B strain lineages of influenza virus have co‐circulated since the mid‐1980s; however, inactivated trivalent influenza vaccines contain only one B lineage. The mismatch between the circulating and vaccine lineages has been a worldwide issue. In this study, an inactivated quadrivalent influenza vaccine (QIV) candidate containing two B lineages was manufactured and its immunogenicity and safety evaluated in an open‐label, uncontrolled trial. In this phase II trial, 50 subjects aged 20–64 years received two doses of QIV s.c. 1 to 4 weeks apart. Sera were collected pre‐ and post‐vaccination and safety assessed from the first vaccination to 21 ± 7 days after the second vaccination. After the first vaccination, hemagglutination inhibition titers against each strain increased markedly; the seroconversion rate, geometric mean titer ratio and seroprotection rate being 94.0%, 24.93, and 100.0%, respectively, for the A/H1N1pdm09 strain; 94.0%, 12.47, and 98.0%, respectively, for the A/H3N2 strain; 54.0%, 4.99, and 66.0%, respectively, for B/Yamagata strain, and 72.0%, 6.23 and 80.0%, respectively, for the B/Victoria strain, thus fulfilling the criteria of the European Medical Agency's Committee for Medicinal Products for Human Use. Also, the QIV induced sufficient single radial hemolysis and neutralizing antibodies against all four vaccine strains. No noteworthy adverse events were noted. The results of this trial demonstrate that QIV is well tolerated and immunogenic for each strain, suggesting that QIV potentially improves protection against influenza B by resolving the issue of B lineage mismatch.